Das Uschebti H 219 im Badischen Landesmuseum und die Chronologie der memphitischen Bürgermeister der 19. Dynastie - Herzberg-Beiersdorf, Anne (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
The inventory number H 219 of the Badisches Landesmuseum Karlsruhe contains the faience shabti of a Memphitic mayor. These civil rulers, subordinate to the king, are mainly responsible for the administration and organisation of the city and its subordinate area, whereby they form the highest regional-administrative instance. Although the Karlsruhe shabti has already been published, its owner has not yet been brought into contact with the circle of Memphite mayors. The aim of this article is to rearrange the chronological order of the known Ramesside officials and to position the owner of the Karlsruhe shabti within this group.